Invasion of common carp (Cyprinus carpio) reduces the quality of bottom sediments in shallow lakes - Joseph S. Rabaey; Brian J. Huser; John A. Downing (Water Research, 2026)

Comparing ecological classifications of freshwater lakes based on reference conditions for benthic invertebrates derived from spatial analogues and paleolimnological approaches - Simon Belle; Richard K. Johnson; Gary Free; Jens Folster; Brian Huser; Sandra Mingarelli (Journal of Environmental Management, 2025)

Continuous phosphorus binding and accumulation in euxinic Baltic Sea sediment a decade after aluminium treatment - Emil Rydin; Brian J. Huser; Oskar Agstam-Norlin; Linda Kumblad (Water Research, 2025)

Towards sustainable lake restoration - Olga Tammeorg; Theis Kragh; Gertrud K. Nürnberg; Laurence Carvalho; Brian Huser; Tom Jilbert; Renata Augustyniak-Tunowska; Tallent Dadi; Kurt Friese; Laura Grinberga; Jolanta K. Grochowska; Sigrid Haande; et al. (Science of The Total Environment, 2025)

Climate Change‐Induced Landscape Alterations Increase Nutrient Sequestration and Cause Severe Oligotrophication of Subarctic Lakes - Willem Goedkoop; Sven Adler; Brian Huser; Hans Gardfjell; Danny C. P. Lau (Global Change Biology, 2025)
We combined decadal data (23–35 y) on nutrient concentrations for nine subarctic lakes with satellite imagery of vegetation (NDVI) to link the ongoing nutrient declines to the climate change‐induced greening of landscapes. Total phosphorus water concentrations (Total‐P) showed declining trends for all nine lakes, ranging from 1.5%–3.6%/y over the last decades. For most of the lakes' drainage areas, NDVI showed a dramatic increase during the 1990s and leveled off between 2001 and 2020. P sequestration in the lakes' drainage areas generally increased by 12%–30% between 1983–1994 and 2001–2020, with an exception of one high‐elevation lake for which P sequestration more than doubled. Area‐specific P‐sequestration estimates for 1983–1994 averaged 1.04 ± 0.10 tons P/km 2 among all lakes but increased by 12%–33% for eight of the nine lakes during 2001–2020. Similar trends were found for nitrogen (N) sequestration, although these were an order of magnitude higher. These estimates illustrate long‐term changes in the sequestration of N and P by terrestrial vegetation in the region. Total‐P and DIN water concentrations showed negative correlations with both the NDVI max of their drainage areas and plot‐scale measurements of tundra dwarf shrub cover. These correlations explained 51.8%–75.4% of the variability in declining nutrient water concentrations and showed the strong links between terrestrial vegetation development and declines in nutrient inputs to downstream lakes. Similar processes are likely ongoing in other parts of the Arctic where vegetation development is progressing, but are either not detected due to the lack of long‐term monitoring data or compensated for by nutrients released from thawing permafrost and/or thermokarst slumps. Upscaling our P‐ and N‐sequestration estimates for the nine lakes to the entire Arctic/alpine ecoregion in Sweden showed an average increase of 12.0 ± 1.7 Mtons P and 122.6 ± 17.5 Mtons N between the periods 1982–1994 and 2001–2020.

Widespread and persistent oligotrophication of northern rivers - Jenny L. Nilsson; Sara Camiolo; Brian Huser; Oskar Agstam-Norlin; Martyn Futter (Science of The Total Environment, 2024)

Trends in mercury, lead and cadmium concentrations in 27 European streams and rivers: 2000–2020 - Karin Eklöf; Claudia von Brömssen; Brian Huser; Staffan Åkerblom; Algirdas Augustaitis; Hans Fredrik Veiteberg Braaten; Heleen A. de Wit; Thomas Dirnböck; David Elustondo; Ulf Grandin; Adéla Holubová; Sirpa Kleemola; et al. (Environmental Pollution, 2024)

A model for predicting reduction in mobile phosphorus of lake sediment by aluminum drinking water treatment residuals - Anthony C. Kuster; Brian J. Huser; Somjate Thongdamrongtham; Santanu Patra; Surapol Padungthon; Anootnara T. Kuster (Water Research, 2023)

Preface: Restoration of eutrophic lakes: current practices and future challenges - Tom Jilbert; Raoul-Marie Couture; Brian J. Huser; Kalevi Salonen (Hydrobiologia, 2020)

Effects of common carp (Cyprinus carpio) on sediment mixing depth and mobile phosphorus mass in the active sediment layer of a shallow lake - Brian J. Huser; Przemyslaw G. Bajer; Christopher J. Chizinski; Peter W. Sorensen (Hydrobiologia, 2016)

Anthropogenic oligotrophication via liming: Long-term phosphorus trends in acidified, limed, and neutral reference lakes in Sweden - Qian Hu; Brian J. Huser (Ambio, 2014)

Amount of phosphorus inactivated by alum treatments in Washington lakes - Emil Rydin; Brian Huser; Eugene B. Welch (Limnology and Oceanography, 2000)
The effectiveness of aluminum (Al) at retaining phosphate was investigated in alum‐treated Washington lake sediments. Greater than background concentrations of Al and Al‐bound phosphorus (Al‐P) were detected in three stratified lakes (Lake Ballinger, Phantom Lake, and Medical Lake) and in three unstratified lakes (Lake Erie, Cambell Lake, and Long Lake). The ratio of added Al to P (Al:Al‐P) was approximately 11:1 by weight in all six lakes. Added Al ranged from 6 to 83 g Al m ‐2 , and adsorbed P subsequently ranged from 0.5 to 7.3 g P m ‐2 . P bound to the added Al was apparently removed from the P cycle, as the layers of increased Al‐P due to treatment were buried in the sediment at a depth corre‐sponding to the approximate time since treatment.